Modulation and recruitment of inducible regulatory T cells by first trimester trophoblast cells - Ramhorst, Rosanna Elizabeth (2012)
Problem The specialized regulatory T-cells (Treg) population, essential for maternal tolerance of the fetus, performs its suppressive actions in the critical peri-implantation phase of pregnancy. In the present work, we investigated whether trophoblast cells are able to induce Treg recruitment, differentiation, and whether these mechanisms are modified by a bacterial or viral infection. Method of Study Human T-regulatory cells were differentiated from naïve CD45RA + CCR7 + cells obtained from peripheral blood mononuclear cells cultured with IL-2 and TGFβ over 5days. Induction of iTregs (CD4 +Foxp3 + cells) was evaluated using low serum conditioned media (LSCM), obtained from two first trimester trophoblast cell lines, Swan-71 and HTR8. Coculture experiments were carried out using transwell assays where trophoblast cells were in the absence or presence of PGN, LPS, or Poly [I:C]. Cytokine production was measured by multiplex analysis. Results Trophoblast cells constitutively secrete high levels of TGFβ and induced a significant increase of Foxp3 expression accompanied by a specific T-reg cytokine profile. Moreover, trophoblast cells were able to recruit iTregs in a specific manner. Conclusion We demonstrate that trophoblast cells have an active role on the recruitment and differentiation of iTregs, therefore, contributing to the process of immune regulation at the placental-maternal interface. © 2011 John Wiley & Sons A/S.